Implications of Innovative Learning for Pendidikan Profesi Guru (PPG) for Increasing Professional Teacher Competence - Sahroni, Sahroni; Subroto, Toto (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The research aimed to study professional development through PPG Innovative Learning and its implications for increasing teacher competency. The aim is to get an overview of the implications of PPG's Innovative Learning on teacher competence. This study uses a particular research approach, namely, using qualitative methods to describe an incident. This research takes a sociological, pedagogical, and psychological perspective. Data collection methods include observation, interviews, and documentation. Data collection and analysis techniques used were data collection as well as data presentation, data reduction, and data triangulation. The results of the study show that Pendidikan Profesi Guru (PPG) was chosen as a solution to overcome these problems, in addition to recognizing the position of teachers as professional educators. Innovative learning continues to be developed to produce professional teachers who are adaptive to change. So, it was concluded that a new position's innovative PPG learning model demands students' readiness, talent, and seriousness to learn independently and with guidance. The implications for professional competence, professional learning practice, and continuing professional development can increase at advanced, appropriate, proficient, or proficient degrees.